Aprovechamiento de los residuos forestales para la elaboración de productos con fines comerciales - Reyes Jipa, Jonathan Geovanni (2021)
This research was carried out in the Buena Fe canton, Los Ríos province, and with the aim of identifying, evaluating and estimating the feasibility of the use of forest residues, in such a way that a model of surveys to the owners was generated. of the different types of round wood collection establishments, thus determining the amount in cubic meters of residual forest biomass produced by these sawmills, of which a total of 19 establishments located in different areas of the Buena Fe canton were located, dedicated to different types of transformation of round wood into various products such as boards, planks, strips, tongue and groove, beams and furniture production mainly for its subsequent commercialization. The different types of stables were evaluated and the proper management and use of the residual forest biomass that is produced during the mechanical transformation process of the wood in the sawmills was determined. The result of this evolution determined that the volume of forest residual biomass is around 1,542.23 m3 per month in all the collection centers located. The majority of establishments do not carry out a correct management of forest residues, since it is given away, stored away and is not used for other commercial purposes, thus generating losses in the volume of residual biomass. Keywords: Residual biomass, evaluation, management and use of wood, wood processing.